THEORETICAL STUDY FOR THE ADSORPTION OF LINEAR PROPADECYL BENZENE SULFONATE (LAS) ON BENTONITE WHICH MODIFIED BY THREE SURFACE ACTIVE MATERIALS - Yasien, Rasha Majeed; Al-Saadie, Khulood (Al-Nahrain Journal of Science, 2018)
Abstract The study included the using of semi-empirical method to calculate the Molecular Orbitals Energies, This calculation let to suggest the best surface active material can be used to modified the adsorption efficiency of LAS (Alkyl benzene Sulfonate) on Iraqi Bentonite by comparison the theoretical results with experimental results which achieved in previous experimental studies between LAS and modified Bentonite by 1-Hexadecylpyridinium bromide (HDPYBr). The theoretical calculation showing the good Efficiency of Hexadecyltrimethyl ammonium chloride (HDTMACl) and 1,12-dipyridiniododecane dibromide (DPYDDBr2), to modified adsorption of LAS on Bentonite. Also a theoretical calculation was made to (HDPYBr) which was studied in previous experimental studies. This study shows that the adsorption efficiency of LAS as the following:- HDPYDDBr2 > HDPYBr > HDTMACl The study including also of the comparison of the stability of the four substance according to the enthalpy of formation which calculated from the theoretical solution, and from the different between the energy of HOMO and LUMO energies levels for the four sub starts.